2006
DOI: 10.1136/bjsm.2005.021139
|View full text |Cite
|
Sign up to set email alerts
|

Counselling increases physical activity behaviour nine weeks after rehabilitation

Abstract: Background: For people with disabilities, a physically active lifestyle can reduce the risk of secondary health problems and improve overall functioning. Objectives: To determine the effects of the sport stimulation programme ''rehabilitation and sports'' (R&S) and R&S combined with the daily physical activity promotion programme ''active after rehabilitation'' (AaR) on sport participation and daily physical activity behaviour nine weeks after inpatient or outpatient rehabilitation. Methods: Subjects in four i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 16 publications
1
74
0
Order By: Relevance
“…Sports may provide training in such complex tasks. Sports are often included in rehabilitation programmes to facilitate their integration into daily life, as it is more difficult to become physically active when sedentary [113]. Enjoyment of sport has also been reported to be a mediator for the adoption of an active lifestyle [93].…”
Section: Presentation Of the Programmementioning
confidence: 99%
“…Sports may provide training in such complex tasks. Sports are often included in rehabilitation programmes to facilitate their integration into daily life, as it is more difficult to become physically active when sedentary [113]. Enjoyment of sport has also been reported to be a mediator for the adoption of an active lifestyle [93].…”
Section: Presentation Of the Programmementioning
confidence: 99%
“…The second personalized, tailored counseling program was called "Active after Rehabilitation" (AaR) and promoted physical activity behavior in general. The results of this intervention study showed that the combination of the R&S and AaR program successfully improved physical activity behavior nine weeks and one year after rehabilitation (van der Ploeg et al, 2006;van der Ploeg et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
“…Subjects in the intervention centers were randomly assigned to the R&S program only, or to both the R&S and AaR intervention programs. However, since the R&S intervention alone was shown to be ineffective (van der Ploeg et al, 2006;van der Ploeg et al, 2007), the current analysis contains only data from the subjects that have received both the R&S and AaR intervention programs and from the control group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations